The development of a plate-based assay to detect the activation status of ARF1 GTPase in Plasmodium falciparum parasites - Du Toit, Skye Carol (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
The exponential rise in antimalarial drug resistance in the most infectious malaria species, Plasmodium falciparum, has emphasised the urgency to identify and validate novel drug targets that decrease parasite viability upon inhibition. In addition to several publications indicating that the regulation of human Arf1 GTPase activity (mediated by ArfGEFs and ArfGAPs) serves as a pertinent drug target for cancer research, the identification of Arf1 and its regulatory proteins in Plasmodium falciparum led to the question whether these protein homologs could be exploited as drug targets for anti-malarial drug therapies. To investigate this prospect, the establishment of a novel in vitro colorimetric ELISA-based assay was needed to be able to detect changes in the activation status of P. falciparum Arf1 (PfArf1) in parasite cultures exposed to potential Arf1 inhibitors. By exploiting the selective protein interaction that occurs between active GTP-bound Arf1 and its downstream effector, GGA3, an assay protocol was established that could be used to detect the activation status of purified, truncated PfArf1 obtained from E. coli and endogenous PfArf1 sourced from parasite lysates. The assay relies on the use of anti-Arf1 antibodies to detect the binding of active PfArf1 in the lysates of inhibitor-exposed cultured parasites to GST-GGA3 immobilised in glutathione-coated plates. The results from chemical validation experiments conducted using the novel assay developed in this study, using the known ArfGEF inhibitor brefeldin A (BFA) and ArfGAP inhibitors Chem1099 and Chem3050, yielded the anticipated results: decrease in active PfArf1 after parasite incubation with the ArfGEF inhibitor, and increased active PfArf1 after ArfGAP inhibition. The results confirmed PfArf1 as a potential anti-malarial drug target and encourages the further development of this assay format for the identification of subsequent inhibitors in library screening campaigns. Additional pilot experiments were conducted to further explore whether the assay could detect the activation status of human Arf1 using HeLa cell lysates and to provide further evidence that the assay could be exploited as a tool in the identification of Arf1 GTPase inhibitors with BFA and the known ArfGAP inhibitor, QS11. The results suggested that, while the assay can detect the increase in active cellular Arf1 due to the inhibition of human ArfGEF following BFA treatment, subsequent treatment with QS11 showed no evidence of a reduction in active human Arf1 due to ArfGAP inhibition. Further experimentation is required to investigate the ability the assay to confirm inhibition of human Arf1 deactivation by ArfGAP inhibitors and develop the assay as a useful tool to support cancer drug discovery, in addition to antimalarial drug discovery projects aimed at Arf1.
Keywords: ARF1; GTPase; Plasmodium falciparum; Malaria; Drug resistance; Drug targeting; Enzyme-linked immunosorbent assay; Proteins